Vibration-Isolation Performance of a Pile Barrier in an Area of Soft Soil in Shanghai - X. F. Ma; M. Y. Cao; X. Q. Gu; B. M. Zhang; Z. H. Yang; P. F. Guan (Shock and Vibration)
Environmental vibration caused by traffic can affect the normal operation of precision instruments, and vibration-isolation measures should be taken to reduce such negative effects. The engineering background of this paper is a hard-X-ray tunnel under construction in Shanghai, China. First, field vibration measurements are used to study the characteristics of the ground traffic, maglev, subway, and other vibration sources near the tunnel, as well as the laws governing the propagation of vibration waves in the surface and soil layer. The finite-element modelling is then used to establish a two-dimensional numerical model for the field conditions, and the numerical results are compared with the field vibration measurements to validate the applicability of the numerical model for assessing the effects of environmental vibration. Finally, how the parameters of a pile-barrier vibration-isolation system, a vibration-isolation measure used widely for tunnels, influence its performance is studied. The results show the following: with increasing distance from the vibration source, the amplitude of the vibration acceleration decreases gradually, and the high-frequency part of the vibration wave is attenuated rapidly, whereas the low-frequency part is attenuated very little. The vibration-isolation effect of the pile barrier is directly proportional to the elastic modulus of the pile body, the pile length, and the hollow ratio of the pile, and inversely proportional to the stiffness of the filling material. The pile diameter, pile row number, and row spacing have little influence on the vibration-isolation effect. Increasing the pile diameter attenuates the acceleration amplitude somewhat around 10 Hz but has no effect on it around 5 Hz. Overall, the present numerical method is well suited to evaluating environmental vibration problems.